Experimental writing: a writer's guide and anthology - Cordeiro, Will 1979-; Lenhart, Lawrence (London, UK; New York, USA: Bloomsbury Academic, 2024)
"An inspiring guide to the practices of contemporary experimental creative writing, this book explores experimentation within both traditional writing genres and 'post-genre' modes such as hybrid texts, Non-creative writing, textual materiality, creative re-purposing, performance and new media technologies. Combining the practices, history, social context, and philosophical backgrounds of experimental work with a broad anthology of models in-book and online, Experimental Writing gives you the toolkit of techniques and skills to confidently engage with forms previously perceived as intimidating so that you can reinvigorate your craft. In addition, the book includes sections on new approaches to the workshop model, emphasis on community and collaboration, and institutional critique. These chapters will provide you with a "big picture" perspective and the motivation to question the templates you work within, giving you the where-with-all to shape your own ideals for writing, no matter what their stylistic choices. Within its broad scope, Experimental Writing covers: - a comprehensive survey of relevant movements, texts, authors, and techniques of non-traditional forms - a survey of evolving trends with exemplars of how genres can be disrupted to help you appreciate experimental styles - demonstrations of how more diverse and innovative pedagogical interventions have the potential to inspire your creativity and create more original work - an examination of the institutional forces that have shaped the creative writing landscape you inhabit, to prompt you to re-examine the pressures, cultural biases, and power structures that have shaped both your aesthetic vision and potential future career paths - frameworks for independent research, practitioner interviews, and motivating questions to get you thinking and questioning before you encounter each new topic With each chapter accompanied by stimulating pedagogical features such as a timeline of experimental writing, free writes, games and constraints, reflections, exercises, prompts and case studies throughout, this invaluable text reveals wider horizon for your artistic endeavors and will activate your critical thinking about a range of issues and ideas"--
Emerging forms : a (dis)orientation -- Hybrids -- Composites & unclassifiables -- Creative repurposing -- Handicrafting & textual materiality -- Conceptual & visual writing -- Minor forms -- Undisciplined writing -- Performance -- Digital writing.
Includes bibliographical references and index.
Keywords: Creative writing; Writing; English Literature; Literature, Experimental